Examining the Effects of Cultural Value Orientations, Emotional Intelligence, and Motivational Orientations: How do LMX Mediation and Gender-Based Moderation Make a Difference? - Tziner, Aharon; Shkoler, Or; Fein, Erich C. (Frontiers in Psychology, 2020)
We examined the role of leader–member exchange (LMX) as a mediator between individual differences and outcomes across three separate studies with 838 participants. Gender-based moderation was used with the LMX mediation effect. Our results suggest that gender makes a dramatic difference. Specifically, we found that LMX mediation lowered the tendency of counterproductive work behaviors (CWBs) for men. In addition, we found that LMX mediated the effect extrinsic motivation has on extrinsic job satisfaction for women. We trace these differences to a tendency for women to express a more democratic and participative leadership style, which implies a different criterion for leader performance in some situations. We also present suggestions for how the findings of our studies can be extended via organizational practice and future research.